PENGARUH MODEL PEMBELAJARAN READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE TERHADAP KEMAMPUAN LITERASI SAINS SIWA KELAS V SDN 101764 BANDAR KLIPPA - Rimma T Purba; Nurhairani; Wildansyah Lubis; Fahrur Rozi; Syahrial (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to test the effect of the read, answer, discuss, explain, and create learning model on the scientific literacy skills of students at SDN 101764 Bandar Klippa. This study uses a quasi-experimental method with a Nonequivalent Control Group design. The research sample consisted of 50 students consisting of 25 students in the experimental class and 25 students in the control class. The data collection technique used a scientific literacy pretest and posttest sheet that had been validated by experts and tested for validity, reliability, discrimination power, and level of difficulty using SPSS 27. The analysis was carried out through the Shapiro-Wilk normality test, Levene's Test homogeneity test, and hypothesis testing using the Independent Sample t-Test. The results showed that there was a significant effect of the RADEC learning model on the scientific literacy skills of fifth-grade students. This was evidenced by the results of the Independent Sample t-Test which obtained a tcount > ttable, namely 2.508 > 2.010 with a significance value of 0.016 (p <0.05), so that the alternative hypothesis was accepted. Descriptively, the average posttest score for the experimental class was 79.2, higher than the control class's score of 70.8. Based on these results, it can be concluded that the RADEC learning model significantly improved the scientific literacy skills of fifth-grade students at SDN 101764 Bandar Klippa.